The Channel Tunnel conference organized jointly by the Institution of Civil Engineers in London and the Societe des ingenieurs et scientifiques de France in Paris, 20-22 September 1989. (Thomas Telford, 1989)
Providing a broad account of the development of the Channel Tunnel project - the most expensive civil engineering project undertaken this century - this book examines the projects financing, management, design and construction.